A study to assess epidemiological, clinical profile and outcome of Monteggia fracture dislocation in adults: a retrospective study - Reddy, G. Ramachandra; Prasad, P. N. (International Journal of Research in Orthopaedics, 2017)
Background: Among all the forearm fractures Monteggia fractures account for approximately 1-2%. Early recognition with anatomical reduction and stable internal fixation is most important in the management of Monteggia fractures. This study was performed to evaluate clinical profile and functional outcome of Monteggia fracture dislocation. Methods: This retrospective study was done on 381 forearm fractures, out of which 31 were Monteggia fracture dislocation. All adults patients who were >20 years were included in the study. Results: During the study period, of 381 cases 31 (8.1%) were having Monteggia fracture dislocation. Most of the study participants were males in (61.2%) compared to females (39%). The cause of the fracture in most of the cases was road traffic accidents accounted by 45%. In most of the cases, the outcome of the operation was excellent (61.3%). Conclusions: If the injury is properly classified and if stable anatomical reduction is achieved at the proper time then the results will always be excellent. In present study all the patients achieved excellent results after surgery.